Asthma control and productivity loss in those with work-related asthma: A population-based study. (28th May 2017) - Wong, Alyson; Tavakoli, Hamid; Sadatsafavi, Mohsen; Carlsten, Chris; FitzGerald, J. Mark
ABSTRACT: Objective : In Canada, asthma is the third leading cause of work loss, yet little is known about the associated productivity loss. The goal of this study was to look at the relationship between asthma control and productivity loss, particularly contrasting those with work-related asthma (WRA) and non-work-related asthma (NWRA). Methods: A population-based random sample of adults with asthma in British Columbia, Canada, was prospectively recruited. Asthma control was graded according to Global Initiative for Asthma classification, while productivity loss and presence of WRA was assessed using questionnaires. Ordinal regression models were then used to associate WRA with asthma control. Generalized linear models were applied to estimate the average productivity loss associated with different levels of asthma control among those with WRA and NWRA. Results: The study included 300 employed adults. Sixty (20%) had WRA. The odds of being controlled were significantly lower in those with WRA (OR = 0.23, 95% CI: 0.09, 0.56; P < 0.01). Those with WRA and uncontrolled asthma had a significant difference in productivity loss due to presenteeism ($659.1 [95% CI: 12.9, 1581.5; P = 0.04]), but not absenteeism ($88.7 [95% CI: −86.5, 279.6; P = 0.35]), when compared to those with NWRA and uncontrolled asthma. There was no significant difference when a similar comparison was made for those with controlled or partially controlled asthma. Conclusions: WRA is associated with worse asthma control and increased productivity loss. Presenteeism makes a significant contribution to productivity loss and should be considered when evaluating the overall economic burden of asthma, particularly WRA.